Immigration And Integration In The United Kingdom - Qurolova Sevinch; Ulmasboyeva Jazira; Dilnoza Shamuratova Jamolovna (Genius Journals, 2024)
This article examines the complex dynamics of immigration and integration in the United Kingdom, focusing on policies, migration patterns, and the surrounding debates. It also delves into the efforts to promote social cohesion, multiculturalism, and integration within British society. Through an extensive review of literature, analysis of policy documents, and evaluation of statistical data, the article provides a detailed understanding of how immigration has shaped the UK and how integration strategies have evolved to foster a harmonious multicultural society
Keywords: Immigration; Integration; UK